Indigenous South African poetry as conduits of History: Epi-poetics – a pedagogy of memory (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
This conceptual article argues that a pedagogy of poetic memory, or epipoetics, can be used to remember and ‘re-member’ the past in the present in the history classroom. Epi-poetics as a theory encapsulates the dynamic interplay of language (including indigenous poetry), the body (both physical and psychological remembering of the past) and the socio-cultural and physical environments in memory construction. As a pedagogy, epi-poetics allows for the indigenisation of the curriculum by tapping into Indigenous Knowledge constructs, specifically indigenous poetry and how it relates to memory, trauma and history. The indigenous poetry is both a source of memory, and, therefore history, and a fount and font of inter-generational experience and trauma.
Keywords: Epi-poetics; Inter-generational memory; Pedagogy; History; Indigenous poetry; Embodiment; Remembrance